c.2 - "Roth, Gabriel" (Oxford, 1987)
This study explores the debate about the appropriate boundary between the roles of the public and private sectors and between government responsibility and private initiative. The author examines ways to engage the resources of the private sector in meeting the needs of developing countries.
Keywords: Privatization- Developing countries